Potential Mechanism of Fatigue Induction and Its Management by JAK Inhibitors in Inflammatory Rheumatic Diseases - Felis-Giemza A; Massalska M; Roszkowski L; Romanowska-Próchnicka K; Ciechomska M (Dove Medical Press, 2023)
Anna Felis-Giemza,1 Magdalena Massalska,2 Leszek Roszkowski,3 Katarzyna Romanowska-Próchnicka,4 Marzena Ciechomska2 1Biologic Therapy Center, National Institute of Geriatrics, Rheumatology, and Rehabilitation (NIGRiR), Warsaw, Poland; 2Department of Pathophysiology and Immunology, National Institute of Geriatrics, Rheumatology, and Rehabilitation (NIGRiR), Warsaw, Poland; 3Department of Outpatient Clinics, National Institute of Geriatrics, Rheumatology, and Rehabilitation (NIGRiR), Warsaw, Poland; 4Department of Biophysics, Physiology and Pathophysiology, Faculty of Health Sciences, Warsaw Medical University, Warsaw, PolandCorrespondence: Magdalena Massalska, Department of Pathophysiology and Immunology, National Institute of Geriatrics, Rheumatology, and Rehabilitation, Spartanska 1, Warsaw, 02-637, Poland, Tel +48226709564, Email magdalena.massalska@spartanska.plAbstract: It is well known that fatigue is a highly disabling symptom commonly observed in inflammatory rheumatic diseases (IRDs). Fatigue is strongly associated with a poor quality of life and seems to be an independent predictor of job loss and disability in patients with different rheumatic diseases. Although the pathogenesis of fatigue remains unclear, indirect data suggest the cooperation of the immune system, the central and autonomic nervous system, and the neuroendocrine system in the induction and sustainment of fatigue in chronic diseases. Fatigue does not correspond with disease activity and its mechanism in IRDs. It is suggested that it may change over time and vary between individuals. Abnormal production of pro-inflammatory cytokines such as interleukin-6 (IL-6), interferons (IFNs), granulocyte-macrophage colony-stimulating factor (GM-CSF), TNF, IL-15, IL-17 play a role in both IRDs and subsequent fatigue development. Some of these cytokines such as IL-6, IFNs, GM-CSF, and common gamma-chain cytokines (IL-15, IL-2, and IL-7) activate the Janus Kinases (JAKs) family of intracellular tyrosine kinases. Therapy blocking JAKs (JAK inhibitors - JAKi) has been recently proven to be an effective approach for IRDs treatment, more efficient in pain reduction than anti-TNF. Therefore, the administration of JAKi to IRDs patients experiencing fatigue may find rational implications as a therapeutic modulator not only of disease inflammatory symptoms but also fatigue with its components like pain and neuropsychiatric features as well. In this review, we demonstrate the latest information on the mechanisms of fatigue in rheumatic diseases and the potential effect of JAKi on fatigue reduction.Plain Language Summary: JAKi block pro-inflammatory cytokines, decrease activation of IDO, diminish the effects of genetic polymorphism (particularly mediated by IL-6 and IL-1β) as well as sickness behavior also connected with IL-1β expression, which result in fatigue and pain inhibition.In patients treated with JAKi, it was observed that there was significantly greater improvement compared to placebo and MTX in fatigue and pain reduction measured using PROs.Administration of JAKi (BARI+UPA) benefits over TNFi treatment in pain and fatigue reduction assessed by PtGA in RA patients.The effectiveness of fatigue reduction in PROs under recently approved JAKi still needs to be proven in clinical practice, especially in selective and nonselective groups of JAKi.Keywords: fatigue, JAK inhibitors, patient-reported outcomes, tofacitinib, baricitinib, upadacitinib